Sobre uma protoóse em Rana catesbiana, Shaw: Nota aos ranicultores brasileiros - Candido M Carvalho , José (Revista Ceres, 1939)
The author reports an ectoprotozoan parasite of Rana catesbiana Show. from Viçosa, Minas Gerais, Brasil. This ciliate (Holotrichida, Tracheliidae) is identical in appearance and dimensions with Amphileptus branchiarum Wenrich, but exact cientific determination could not he made because of the lack of adequate literature.